The Quantitative Evaluation of Palatal Elongation after Furlow Palatoplasty - Guneren, E; Uysal, OA (W B Saunders Co-Elsevier Inc, 2004)
Purpose: Furlow "double-opposing Z-palatoplasty" (FP) operation lengthens the soft palate by using only soft palate tissues. It is used in cleft palate repair and velopharyngeal incompetence. The aim of this study was to define the importance of the length and ratio of the soft palate elongation after FP. Patients and Methods: This study included 17 patients who were operated on by the same surgeon using FP. The mean follow-up period time was 4.5 years. Preoperative, intraoperative, and late postoperative velar lengths were measured and elongation ratios were calculated. Results: Mean intraoperative elongation and ratio were 16.11 mm and 69.05%, and mean late postoperative elongation and ratio were 12.47 mm and 55.47%, respectively. Conclusion: Significant and permanent elongation in velar length was obtained using the FP. (C) 2004 American Association of Oral and Maxillofacial Surgeons.